Immunoturbidimetric assay of glycated hemoglobin - Metus, Paolo (J Clin Lab Anal, 1999)
We investigated the performances of HbA1c determination by a latex enhanced turbidimetric immunoassay using the specific monoclonal antibodies (Unimate, Roche) against the β‐N‐terminal fragments. The coefficients of variation ranges from 1.7 to 3.8% within assay (n = 30) and from 3.9 to 4.9% between assay (n = 20). The assay was linear from 2.5 to 14.9% of HbA1c. No interferences was found from fetal, carbamylated, or variant (S) hemoglobins and from labile Schiff adduct with glucose. The following relationship was derived from fresh sample comparison between HPLC (Diamat‐BioRad) (x) and immunoassay (y) method: y = 0.971 x + 0.87%, r = 0.98, n = 115. The immunoassay provides a highly precise and specific method for HbA1c. J. Clin. Lab. Anal. 13:5–8, 1999. © 1999 Wiley‐Liss, Inc.